The effect of cold on performance and muscle damage during intensive training - Kapilevich L.V.; Wang Ya.; Li T.; Negodenko E.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to аssessing the effects of cold immersion on muscle damage and performance during intense training. Methods and structure of the study. A meta-analysis of publications was performed on the problem of using cold immersion for the purpose of recovery after physical activity. Using the keyword cold water immersion, 2,650 articles were found over the past 20 years, and when adding the words sport and/or exercise, 703 results were found. 120 articles with the highest citation index were selected based on the five-year period after the article was published. Results and conclusions. Most of the work indicates the positive effects of cold immersion on recovery processes after intense physical activity. At the same time, positive effects are recorded mainly when using a temperature not lower than 10-15 ° C and a duration of over 15 minutes (or two short sessions with a small interval) and appear within the first day. Refrigeration at lower temperatures must be used with caution. It is also not recommended to exercise during the first hours after the cold immersion procedure.